Assessment of the effect of occupational exposure to formaldehyde on the risk of lung cancer in two Canadian population-based case-control studies - Amel Mahboubi; Anita Koushik; Jack Siemiatycki; Jérôme Lavoué; Marie-Claude Rousseau (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: This study aimed to explore the possible association between formaldehyde exposure and lung cancer risk. METHODS: Data were collected in two population-based case-control studies conducted in Montreal, Canada. Cases were individuals diagnosed with incident, histologically-confirmed lung cancer. Controls were randomly selected from electoral lists and frequency-matched to cases by age, sex, and electoral district of residence. Interviews for the two studies were conducted in 1979-1986 and 1996-2002, using a virtually identical questionnaire to obtain lifetime occupational and smoking history and several lifestyle covariates. Experts reviewed the detailed work history for each participant to assess exposure to several occupational agents, including formaldehyde. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (95% CI) for the associations between several metrics of formaldehyde exposure and lung cancer, adjusting for smoking and occupational and sociodemographic factors. RESULTS: In all, 2060 lung cancer cases and 2046 population controls were interviewed and assessed for exposure. About 25% of subjects had ever been occupationally exposed to formaldehyde. The adjusted OR for lung cancer was 1.06 (95% CI 0.89-1.27) comparing ever versus never exposure to formaldehyde. Analyses for age at first exposure, average, and peak intensity of exposure also suggested an absence of association between formaldehyde exposure and lung cancer risk. Results did not vary by sex, lifetime smoking intensity, or histological subtype. CONCLUSIONS: No marked increases in lung cancer risk related to workplace formaldehyde exposure were observed. Study participants were mainly exposed at low concentration levels, which should be considered in the interpretation of our findings.